Aplicación del proceso de atención de enfermería en recién nacido pretérmino con dificultad respiratoria. - Erazo Aguirre, Genesis Andrea (2021)
In The present clinical case study applies the process of nursing care in a preterm newborn with respiratory distress pathology which is characterized by the lungs of premature neonates having surfactant deficit, causing the inability to maintain an adequate gas exchange. The clinical case that is written below was carried out in the University Pediatric Obstetric Gynecology Hospital of Guayaquil, it is a female newborn with 34 weeks of gestation which enters the NICU room presenting a clinical picture of dyspnea, nasal flutter, cyanotic, through the relevant assessments and laboratory examinations performed, it was possible to corroborate that it was a diagnosis of respiratory distress. To then apply the nursing care process NANDA, NIC AND NOC identifying the altered functional patterns, carrying out the respective follow-up and providing the pertinent nursing care, resulting in a good evolution of the newborn.